Correction: Enhanced photoluminescence stability and internal defect evolution of the all-inorganic lead-free CsEuCl3 perovskite nanocrystals. Issue 36 (13th September 2022) - Gao, Yalei; Zhang, Tao; Liu, Jun; Liu, Hongjun; Li, Meixian; Liu, Fuchi; Kong, Wenjie; Lv, Fengzhen; Yang, Yong; Long, Lizhen
Abstract : Correction for 'Enhanced photoluminescence stability and internal defect evolution of the all-inorganic lead-free CsEuCl3 perovskite nanocrystals' by Yalei Gao et al., Phys. Chem. Chem. Phys., 2022, 24, 18860–18867, ; https://doi.org/10.1039/D2CP01374F .